A Fatal Case of Erdheim‐Chester Disease with Hepatic Involvement. Issue 1 (2017) - Balasubramanian, Gokulakrishnan; Modiri, Alexandra; Affi, Marina; Hagen, Catherine E.; Batdorf, Bjorn; Oshima, Kiyoko; Michaelis, Laura; Saeian, Kia
ABSTRACT : N/A: Erdheim‐Chester disease (ECD) is a rare form of systemic histiocytosis, typically presenting with striking osseous involvement characterized by bilateral osteosclerosis and involvement of organs such as the lung, pituitary gland, heart, and brain. Liver involvement with ECD is extremely uncommon. We report a 56‐year‐old woman presenting with newly diagnosed cirrhosis and signs concerning for intra‐abdominal malignancy, including omental caking and peritoneal thickening. Liver biopsy demonstrated xanthogranulomatous infiltration from ECD. The patient showed initial improvement with interferon therapy, but she developed severe depression, which led to the discontinuation of the treatment. Shortly afterward, she died from progressive liver dysfunction resulting in hepatorenal syndrome.